2019
DOI: 10.3390/ijgi8040174
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Geostatistical, Machine Learning, and Hybrid Approaches for Mapping Topsoil Organic Carbon Content

Abstract: Accurate digital soil mapping (DSM) of soil organic carbon (SOC) is still a challenging subject because of its spatial variability and dependency. This study is aimed at comparing six typical methods in three types of DSM techniques for SOC mapping in an area surrounding Changchun in Northeast China. The methods include ordinary kriging (OK) and geographically weighted regression (GWR) from geostatistics, support vector machines for regression (SVR) and artificial neural networks (ANN) from machine learning, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 77 publications
1
27
0
2
Order By: Relevance
“…OK is a geostatistical technique and is widely used. Based on regionalized variables, it can generate an optimal unbiased estimated surface based on a semivariogram [15]. This semivariogram can be constructed with GS+ (version 9.0, Leland Stanford Junior University, Stanford, CA, USA).…”
Section: Algorithm Development and Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…OK is a geostatistical technique and is widely used. Based on regionalized variables, it can generate an optimal unbiased estimated surface based on a semivariogram [15]. This semivariogram can be constructed with GS+ (version 9.0, Leland Stanford Junior University, Stanford, CA, USA).…”
Section: Algorithm Development and Predictionsmentioning
confidence: 99%
“…Studies revealed that the prediction techniques for soil attributes are based mainly on spatial correlation, including autocorrelation and mutual correlation [14]. Commonly used autocorrelation technologies include inverse distance weighting (IDW) and ordinary kriging (OK) [15]. Spatial mutual-correlation-based predictions integrate field observations and environmental variables through quantitative relationships [16].…”
mentioning
confidence: 99%
“…Remote sensing has unique advantages in monitoring frontier lands, which are always in remote and difficult-to-reach locations. Examples have included: satellite-observed dynamics of lake-rich regions across the Tibetan Plateau and the Arctic; forest disturbance and dynamics in Siberia; the assessment of the complex Amur tiger and Far Eastern leopard habitats in the Russian Far East; in the landscape and ecosystem characterizations in China and Southeast Asia; in conservation efforts of tree kangaroos in Papua New Guinea; and in PAs in the Albertine Rift of Africa [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Remote sensing has advantages in monitoring vast habitats both inside and surrounding the PAs.…”
Section: Remote Sensing Applications In Monitoring Of Protected Areasmentioning
confidence: 99%
“…Remote sensing has unique advantages in monitoring frontier lands, which are always in remote and difficult-to-reach locations. Examples have included: satellite-observed dynamics of lake-rich regions across the Tibetan Plateau and the Arctic; forest disturbance and dynamics in Siberia; the assessment of the complex Amur tiger and Far Eastern leopard habitats in the Russian Far East; in the landscape and ecosystem characterizations in China and Southeast Asia; in conservation efforts of tree kangaroos in Papua New Guinea; and in PAs in the Albertine Rift of Africa [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Remote sensing has advantages in monitoring vast habitats both inside and surrounding the PAs.…”
Section: Remote Sensing Applications In Monitoring Of Protected Areasmentioning
confidence: 99%